Retinal and Optic Nerve Degeneration in Patients with Multiple Sclerosis Followed up for 5 Years - Garcia-Martin, Elena; Ara, Jose R; Martin, Jesus; Almarcegui, Carmen; Dolz, Isabel; Vilades, Elisa; Gil-Arribas, Laura; Fernandez, Francisco J; Polo, Vicente; Larrosa, Jose M; Pablo, Luis E; Satue, Maria (Ophthalmology (Rochester, Minn.), 2017)
To quantify retinal nerve fiber layer (RNFL) changes in patients with multiple sclerosis (MS) and healthy controls with a 5-year follow-up and to analyze correlations between disability progression and RNFL degeneration. Observational and longitudinal study. One hundred patients with relapsing-remitting MS and 50 healthy controls. All participants underwent a complete ophthalmic and electrophysiologic exploration and were re-evaluated annually for 5 years. Visual acuity (Snellen chart), color vision (Ishihara pseudoisochromatic plates), visual field examination, optical coherence tomography (OCT), scanning laser polarimetry (SLP), and visual evoked potentials. Expanded Disability Status Scale (EDSS) scores, disease duration, treatments, prior optic neuritis episodes, and quality of life (QOL; based on the 54-item Multiple Sclerosis Quality of Life Scale score). Optical coherence tomography (OCT) revealed changes in all RNFL thicknesses in both groups. In the MS group, changes were detected in average thickness and in the mean deviation using the GDx-VCC nerve fiber analyzer (Laser Diagnostic Technologies, San Diego, CA) and in the P100 latency of visual evoked potentials; no changes were detected in visual acuity, color vision, or visual fields. Optical coherence tomography showed greater differences in the inferior and temporal RNFL thicknesses in both groups. In MS patients only, OCT revealed a moderate correlation between the increase in EDSS and temporal and superior RNFL thinning. Temporal RNFL thinning based on OCT results was correlated moderately with decreased QOL. Multiple sclerosis patients exhibit a progressive axonal loss in the optic nerve fiber layer. Retinal nerve fiber layer thinning based on OCT results is a useful marker for assessing MS progression and correlates with increased disability and reduced QOL.